Wasilah al-Kharithah al-Mafahim fi Ta’lim ‘Ilm al-Sharf li Tulab al-Jami’iy - Mufidah, Nuril; Mukadam, Abdur-Rasheed Mahmoud; Ahadi, Ahmad Fibrian Nurul; Taufiqurrochman, R (Universitas Islam Negeri Raden Intan Lampung, 2019)
Shorof is an essential tool in learning Arabic and a prerequisite for mastering Arabic. The problem that is often encountered in the learning process that takes place is the difficulty of students in mastering the material memorization because learning is only centered on lecture theory. The solution to this problem is to provide learning media concept maps which are often referred to as concept mapping. The method used in this research is qualitative research with the object of 3rd-semester Arabic language education students Maulana Malik Ibrahim State Islamic University Malang, amounting to 50 students. Also, students at the second level in the Department of Arabic at Ilorin University, Ilorin Nigeria, there are 40 students. Concept maps are designed by linking the concept of propositions using conjunctions with giving lines that are labeled so that they have a meaning. By applying this method, it will affect the ease of students in understanding the material in learning. Based on the research conducted, data differences were obtained between the data on the results of student learning achievements in the study of the students who did not use media concept mapping with those using the concept mapping. That the results of student achievement are better when using these media. Then it can be concluded that there is a significant effect of the use of media concept mapping in the study of theorists.